2011
DOI: 10.3945/ajcn.110.004028
|View full text |Cite
|
Sign up to set email alerts
|

Diet, vegetarianism, and cataract risk

Abstract: Background: Age-related cataract is a major cause of morbidity. Previous studies of diet and cataract risk have focused on specific nutrients or healthy eating indexes but not on identifiable dietary groups such as vegetarians. Objective: We investigated the association between diet and cataract risk in a population that has a wide range of diets and includes a high proportion of vegetarians. Design: We used Cox proportional hazards regression to study cataract risk in relation to baseline dietary and lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 38 publications
4
71
0
3
Order By: Relevance
“…In the European Prospective Study Investigation in Cancer and Nutrition (EPIC),high intakes of vitamin A were also associated with increased risk of “any” cataract (IRR [incidence risk ratio] = 1.28; 95%CI: 1.07–1.54) (Figure S25). 88 …”
Section: Newer Epidemiologic Studies That Relate Carotenoids and Vitamentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Prospective Study Investigation in Cancer and Nutrition (EPIC),high intakes of vitamin A were also associated with increased risk of “any” cataract (IRR [incidence risk ratio] = 1.28; 95%CI: 1.07–1.54) (Figure S25). 88 …”
Section: Newer Epidemiologic Studies That Relate Carotenoids and Vitamentioning
confidence: 99%
“…89 Although the EPIC did not find any association between risk of “any” type of cataract and intakes of thiamin, riboflavin, niacin, or folate, it did report an increased risk among those with elevated vitamin B 12 intake (IRR = 1.29; 95%CI: 1.06–1.56) (Figure S28). 88 …”
Section: Newer Epidemiologic Studies That Relate Carotenoids and Vitamentioning
confidence: 99%
“…This study also found a strong inverse association between dietary fibre intake and diverticular disease risk, but both associations remained statistically significant after mutual adjustment. Other analyses in EPIC-Oxford showed that vegetarians (including vegans) were at lower risk of eye cataract compared with meat eaters (relative risk 0·74, 95 % CI 0·63, 0·86), with a progressive reduction in risk from high (at least 100 g/d) to low (<50 g/d) intake meat eaters, fish eaters, lacto-ovo-vegetarians and vegans (52) . Vegetarians in the EPIC-Oxford study also had a 31 % (95 % CI 2, 52) lower risk of kidney stones compared with participants consuming a high meat diet (53) .…”
Section: Other Diseases and Conditionsmentioning
confidence: 99%
“…1% (p = 0.000135) in Pathanamthitta and 87.1% (p = 0.000265) in Kottayam than vegetarians. Vegetarians were at lower risk of cataract than were meat eaters in the cohort of health-conscious British residents [20] . Laboratory, clinical, epidemiologic and animal data support the association between cataract prevention and diet supplements such as riboflavin, vitamin C, vitamin E and Caroteniods [21,22] .…”
Section: Discussionmentioning
confidence: 99%